Karakteristik Geospasial Sebagai Dasar Perencanaan Untuk Memperkuat Ketahanan Perbatasan NKRI (Studi Kasus; Perencanaan Kota Perbatasan Distrik Sota-PNG, Merauke, Provinsi Papua) - Agustan Latif; Agustan Agustan (Universitas Gadjah Mada, 2017)
ABSTRACTThis is a national strategic study of border areas because it has significance for the sovereignty, defense and security of the easternmost regions of Indonesia - Papua New Guinea. The purpose of this research is focused on the characteristics of geospatial data to support of the border city tourism plan in Sota of Merauke Regency (Border RI - PNG). Based on the result of an investigation of planning document from spatial plan of Merauke regency directing sota as non-agricultural area with indication of development of urban area and residential center, while from National Park of wasur as authority of national park management show direction of sota area development as development zone with indication of tourist destination. The research recommends several things in the management of border areas such as: It is necessary to strengthen the social and cultural fields, improving the infrastructure, especially the public services, the strengthening of human resources and the supervision of the environment. Meanwhile, in encouraging the acceleration of development in the border area of sota need to increase coordination between the central government, provincial and regional Merauke regency.ABSTRAKPenelitian ini merupakan kajian strategis nasional kawasan perbatasan karena memiliki arti penting bagi kedaulatan, pertahanan dan keamanan negara khususnya wilayah paling timur Indonesia – Papua Nugini. Secara khusus tujuan penelitian ini difokuskan pada karakteristik data geospasial dalam mendukung rencana kota wisata perbatasan di Sota Kabupaten Merauke (Perbatasan RI – PNG). Berdasarkan hasil investigasi dokumen perencanaan dari rencana tata ruang kabupaten Merauke mengarahkan sota sebagai kawasan non pertanian dengan indikasi pengembangan kawasan perkotaan dan pusat pemukiman, sedangkan dari balai Taman Nasional wasur sebagai otoritas pengelola taman nasional menunjukkan arahan pengembangan wilayah sota sebagai zona pengembangan dengan indikasi tujuan wisata. Hasil penelitian merekomendasikan beberapa hal dalam pengelolaan wilayah perbatasan sota diantaranya: Perlu adanya penguatan bidang sosial dan budaya, peningkatan infrastruktur khusu pelayanan umum, penguatan sumber daya manusia, dan pengawasan linkungan. Sedangkan dalam mendorong percepatan pembangunan di kawasan perbatasan sota perlu adanya peningkatan koordinasi antara pemerintah pusat, provinsi dan daerah kabupaten Merauke.